CLF Embodied Carbon Toolkit for Roadway Infrastructure Part 1: Introduction to Embodied Carbon and Roadway Infrastructure - Ashtiani, Milad; Lewis, Meghan; Waldman, Brook; Simonen, Kate (My University, 2024)
Greenhouse gas emissions released due to the manufacturing, transportation, and installation of products are collectively known as embodied carbon. Embodied carbon can be released during any stage of a transportation infrastructure life cycle including the initial construction, maintenance, and the end of life. Embodied carbon due to the construction and maintenance of roadways is a large contributor to overall GHGs attributed to transportation agencies owning and managing these public assets. This toolkit aims to help departments of transportation (DOTs) and other transportation agencies better understand the sources of GHG emissions from building the roadway infrastructure.